Designing the networked enterprise - Igor Hawryskiewycz (Artech House, 1997)
The new environment; Working in the networked enterprise; Groups; Processes and workflows; The changing organization; Interfaces for collaborative work; Plaforms; Networks; Commerce on the internet; Platforms for collaborative systems; Repositories and coauthoring; Workflows; Meeting and conferences; Building cooperative systems; Analyzing work practices...